Biosimilar infliximab use in paediatric IBD. Issue 1 (7th October 2017) - Richmond, Lisa; Curtis, Lee; Garrick, Victoria; Rogers, Pam; Wilson, Michelle; Tayler, Rachel; Henderson, Paul; Hansen, Richard; Wilson, David C; Russell, Richard K
Abstract : Background: Biosimilar infliximab became available in the UK in 2015. Paediatric experience to date on its use is limited. We prospectively evaluated the safety and efficacy of biosimilar infliximab (Remsima) in two paediatric gastroenterology networks in patients with inflammatory bowel disease. Methods: Prospective clinical data were collected from laboratory reports, electronic patient records and case notes of 40 patients starting Remsima for the first time. Disease activity scores together with blood and stool biomarkers were used to assess response. Results: Our data set highlights that Remsima was associated with a significant clinical and biochemical improvement (p<0.01 or less for all parameters assessed) in Crohn's disease post induction. There were no significant safety issues noted. The total cost saving was £47 800, representing a 38% reduction from originator. Conclusion: We found that biosimilar infliximab is as effective as originator infliximab and its use is associated with significant cost savings.